Computational design and cheminformatics profiling of omeprazole derivatives for enhanced proton pump inhibition of potassium-transporting ATPase alpha chain 1 - Mahmudul Hasan; Md. Ifteker Hossain; Noimul Hasan Siddiquee; Ezaz Ahmed; Md Walid Hossain Talukder; Md Rahamatolla; Tasrin Nahar; Popy Rani Paul; Mahmudul Hassan Suhag; Monir Uzzaman (PLoS ONE, 2025)
Proton pump inhibitors are essential for treating moderate-to-severe gastroesophageal reflux, peptic ulcers, esophagitis, and related conditions by increasing gastric pH and inhibiting hydrogen ion discharge into the stomach. However, prolonged use may lead to adverse effects along with reduced efficacy. Our research investigates the strategic modification of omeprazole (OMP) derivatives to improve their binding affinity to targeted proteins, thereby enhancing their chemical reactivity, stability, and toxicity profiles. A total of 22 novel OMP analogues were designed through structural alterations, focusing on the benzimidazole and pyridine rings. The geometrical attributes of the analogues were further confirmed through spectral and quantum computational analysis based on density functional theory (DFT) and a B3LYP/6-31G+ G (d, p) basis set. The molecular docking with PTAAC1 presented that most of the analogues had similar or higher binding affinities and nonbonding interactions, including OMP3, OMP19, and OMP21, with binding energies of -7.3, -8.3, and -8.1 kcal/mol compared to the OMP at -7.1 kcal/mol. Pharmacokinetic, biological, and toxicological profiles via ADMET and PASS predictions also demonstrated increased safety and therapeutic potential. MD simulation also showed good stability of OMP3, OMP19, and OMP21 in binding to PTAAC1, and the RMSD, RMSF, ligand RMSD, rGyr, SASA, MolSA, PolSA, and hydrogen bond analysis also suggested superior drug potential compared to OMP. Additionally, the post-simulation MM/GBSA analysis revealed that OMP3 (-36.91 kcal/mol) outperformed OMP19 (-26.45) and OMP21 (-12.61). The protein binding site’s high stability and elevated negative binding free energy value further indicate a robust compound-protein interaction with OMP3. However, principal component analysis (PCA) showed the highest variance for OMP21, accounting for 50.66%, 21.58%, and 6.51%, respectively, for PC1, PC2, and PC3. These findings could lead to the development of OMP3 and OMP21 as potential next-generation PPIs with enhanced pharmacological activity and improved side-effect profiles, necessitating more in vitro and in vivo testing.